The Grounded Theory Bookshelf - Vivian B. Martin (Grounded Theory Review: An International Journal)
Bookshelf will provide critical reviews and perspectives on books on theory and methodology of interest to grounded theory. This issue includes a review of Heaton’s Reworking Qualitative Data, of special interest for some of its references to grounded theory as a secondary analysis tool; and Goulding’s Grounded Theory: A practical guide for management, business, and market researchers, a book that attempts to explicate the method and presents a grounded theory study that falls a little short of the mark of a fully elaborated theory.